THE EFFECT OF DECORATED SPICED DRINK ON TOTAL CHOLESTEROL AND BLOOD GLUCOSE LEVELS IN PATIENTS WITH HYPERCHOLESSOROLEMIA - Khansa Fatin Salsabila; Nurmeily Rachmawati; Venny Patricia (Poltekkes Kemenkes Banten, 2026)
Hypercholesterolemia is one of the main risk factors for cardiovascular diseases that can be influenced by lifestyle and dietary patterns, including the consumption of herbs or spices. This study aims to determine the effect of administering herbal drink decoctions on total cholesterol levels and random blood glucose in patients with hypercholesterolemia. This study uses a Quasi-Experiment method with control and treatment groups design. The research subjects were divided into two groups: one group received the herbal drink decoction and the control group received no treatment. The parameters measured were total cholesterol levels and random blood glucose through laboratory tests before and after the treatment. The results of this study showed that the average cholesterol level in the treatment group before the intervention was 220 mg/dL, and after the intervention to 210 mg/dL. The results of total cholesterol levels in the control group before the intervention amounted to 173 mg/dL, for after the intervention to 185 mg/dL. The results for blood glucose levels in the treatment group before the intervention were 92 mg/dL and after the intervention to 97 mg/dL. Then for the results of temporary blood glucose levels in the control group before the intervention amounted to 88 mg/dL and after the intervention amounted to 90 mg/dL).The results of the statistical tests showed that H0 was accepted, which means there was no significant effect of administering herbal drink decoctions on total cholesterol levels and random blood glucose. Thus, the herbal drink infusion was not proven effective in lowering both parameters in patients with hypercholesterolemia. This study was conducted in the Pondok Kacang Barat area.